Analysis of Learning Outcomes and Evaluation Questions in the Computer Science Book for the Twelfth Grade for Academic and Professional Branches in Jordan according to Bloom’s cognitive levels - Al- Amoush, Alia Mohsen (Journal of Educational and Psychological Sciences, 2020)
This study aimed to Analysis the learning Outcomes and evaluation questions in the computer science book for the twelfth grade for academic and professional branches in Jordan according to Bloom’s cognitive levels. The community and the sample consisted of the (64) outcomes, and (99) major questions, includes (219) sub- questions, where the objective and the sub- question was considered as a unit of analysis. The researcher adopted the intentional method in selecting the sample, and used the descriptive analytical approach to conduct the study, where he used a card to analyze the levels of cognitive goals according to the Bloom’s taxonomy. The searcher used percentages and the arithmetic mean of the statistical treatment, the results showed that the computer science textbook questions do not reflect the educational outcomes in light of bloom taxonomy. On the other hand the outcomes and the questions focused on the lowest thinking levels, where the educational outcomes came with (94%) distributed on the remembering (59%), and applying (28%), and understanding (6%). While the questions focus on the lowest thinking levels with percent of (98%) distributed on the remembering (46%), and applying (35%), and understanding (16%). While it showed weakness in the focus on the higher thinking levels, the level of (analyze) got (6%) for the educational outcomes, and (2%) for the questions, and there were no levels of synthesis and evaluation. The study recommended that the learning outcomes and evaluation questions should be distributed over all of the knowledge dimensions, especially higher thinking levels, and trains the writer of the questions in preparing and formulating the questions in a manner consistent with cognitive levels of Bloom’s classification.